Strengthening Character Education (Adab) Through Islamic Religious Education (PAI) in Islamic Elementary Schools - Uri, Fatimah; Harahap, Nasrun (Universitas Trunojoyo Madura, 2025)
This study examines the critical role of Islamic Religious Education (PAI) in strengthening character education (adab) among students in Islamic elementary schools, with a focus on internalizing moral and ethical values to cultivate noble behavior. Using a qualitative literature review method, this research synthesizes data from scholarly articles, books, and policy documents related to PAI-based character education. The findings highlight three key strategies for fostering adab: (1) teacher exemplification, where educators model Islamic values in daily interactions; (2) habitual practice, such as structured routines for prayer, honesty, and respect; and (3) creating a supportive school environment that reinforces Islamic ethics through rules, culture, and peer interactions. However, challenges such as limited parental involvement and the negative influence of digital media hinder consistent implementation. The study concludes that effective adab integration requires a holistic approach, combining curriculum design, school culture, and community engagement. When systematically applied, PAI can transform students' moral development, ensuring they not only understand Islamic teachings but also embody them in daily life. These insights contribute to improving Islamic education strategies for character building in modern contexts.This study examines the critical role of Islamic Religious Education (PAI) in strengthening character education (adab) among students in Islamic elementary schools, with a focus on internalizing moral and ethical values to cultivate noble behavior. Using a qualitative literature review method, this research synthesizes data from scholarly articles, books, and policy documents related to PAI-based character education. The findings highlight three key strategies for fostering adab: (1) teacher exemplification, where educators model Islamic values in daily interactions; (2) habitual practice, such as structured routines for prayer, honesty, and respect; and (3) creating a supportive school environment that reinforces Islamic ethics through rules, culture, and peer interactions. However, challenges such as limited parental involvement and the negative influence of digital media hinder consistent implementation. The study concludes that effective adab integration requires a holistic approach, combining curriculum design, school culture, and community engagement. When systematically applied, PAI can transform students' moral development, ensuring they not only understand Islamic teachings but also embody them in daily life. These insights contribute to improving Islamic education strategies for character building in modern contexts.